Fiscal Deficit, Taxing and Effective Demand - Alarco Tosoni, Germán (1985)
The objective of this work is to present a vision contrary to the liberal one, in which the ineffectiveness of the public sector is the consequence of the actions of the executors of economic policies. Here it is asked how the different variables are theoretically linked to the concept of “effectiveness of public sector actions” and it will be contrasted with the historical experience of the recent years. It also pretends to show that the theoretical approach of the public deficit related to the executors of economic policy corresponds to a particular theoretical option subject to strong criticism. Finally, it wants to stand out that this is a first partial (and general) attempt to propose a general hypothesis to tackle the public problem from a Keynesian-Kaleckian approach to reality.